Improvement of the Culture Medium for the Dichlorvos-Ammonia (DV-AM) Method to Selectively Detect Aflatoxigenic Fungi in Soil - Kimiko Yabe; Haruna Ozaki; Takuya Maruyama; Keisuke Hayashi; Yuki Matto; Marika Ishizaka; Takeru Makita; Syun-ya Noma; Kousuke Fujiwara; Masayo Kushiro (Toxins, 2018)
The dichlorvos-ammonia (DV-AM) method is a simple but sensitive visual method for detecting aflatoxigenic fungi. Here we sought to develop a selective medium that is appropriate for the growth of aflatoxigenic fungi among soil mycoflora. We examined the effects of different concentrations of carbon sources (sucrose and glucose) and detergents (deoxycholate (DOC), Triton X-100, and Tween 80) on microorganisms in soils, using agar medium supplemented with chloramphenicol. The results demonstrated that 5⁻10% sucrose concentrations and 0.1⁻0.15% DOC concentrations were appropriate for the selective detection of aflatoxigenic fungi in soil. We also identified the optimal constituents of the medium on which the normal rapid growth of Rhizopus sp. was completely inhibited. By using the new medium along with the DV-AM method, we succeeded in the isolation of aflatoxigenic fungi from non-agricultural fields in Fukui city, Japan. The fungi were identified as Aspergillus nomius based on their calmodulin gene sequences. These results indicate that the new medium will be useful in practice for the detection of aflatoxigenic fungi in soil samples including those from non-agricultural environments.